Heavy rainfall events over southeast peninsular India during northeast monsoon: Role of El Niño and easterly wave activity. (2nd December 2018) - Sanap, S. D.; Priya, P.; Sawaisarje, G. K.; Hosalikar, K. S.
Abstract : The catastrophic floods over southeast peninsular India during 2015 northeast monsoon season (NEM, October–December) avowed 400 lives, affected more than 4 million people and reported a loss of property worth 3 billion US dollars. In the present study, an attempt has been made to understand the mechanism of occurrence of heavy rainfall events over southeast peninsular India during NEM, with a special emphasize on 2015 heavy rainfall events. In presence of strong El Niño, basin‐wide warming and low‐level easterly winds were observed over tropical Indian Ocean during NEM‐2015. It is noted that dominant easterly wave (EW) activity aided the intensification of already developing synoptic systems over Bay of Bengal (BoB) and led to occurrence of heavy rainfall events. This finding encouraged us to explore the association of El Niño, EW activity and heavy rainfall occurrences over southeast peninsular India during NEM for the period 1951–2015. It is noticed that ~43% of the heavy rainfall events during NEM are associated with El Niño, ~31% with La Niña and ~26% with neutral years, respectively. A 3–7‐day band‐pass filter is applied to the daily global reanalysis fields to elucidate the role of EW activity on heavy rainfall occurrences over the region during El Niño–Southern Oscillations (ENSO). Results indicate that EW activity over Indian Ocean plays a seminal role in occurrence of the heavy rainfall events during positive phase of the ENSO (El Niño), while it is found to be weak during negative (La Niña) and neutral phase. It is also revealed that significant above‐normal sea surface temperature (SST) over BoB, strong west–east SST gradient between southwest BoB and tropical western Pacific Ocean and anomalous strong low‐level easterly flow over tropical Indian Ocean during El Niño years offer favourable conditions for the initiation and westwards propagation of EWs. Abstract : Time evolution of the 3–7‐day filtered composite anomalies of 700 hPa wind and relative vorticity (×10 −5 S −1, shaded) for El Niño years in which heavy rainfall occurred from Day −5 to Day 0 (day of occurrence of heavy rainfall).